Mooring Design and Fatigue Damage on Variant Fairlead Positions During FPSO Operation – Case Study (Maritime Park: Journal of Maritime Technology and Society, 2024)
This comprehensive case study delves into the intricate dynamics of deepwater mooring systems, specifically focusing on Floating Production Storage and Offloading (FPSO) operations. Our investigation centers on the Anoa Natuna FPSO, situated in the Arafura Sea. We examine how varying fairlead positions, employing a 4x3 chain configuration, influence structural integrity, operational stability, and fatigue damage. The research meticulously analyzes the response of the FPSO to environmental forces, providing a detailed understanding of the vessel's behavior under different fairlead positions. The results showcase the vessel's stability, elucidate variations in its motion response, and highlight the effects of fairlead positioning on structural fatigue, offering valuable insights for safe and efficient deepwater FPSO operations.
Keywords: Fairlead position; Fatigue damage; Mooring systems